2017
DOI: 10.1080/00140139.2017.1314023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three methods for evaluation of work postures in a truck assembly plant

Abstract: This study compared the results of three risk assessment tools (self-reported questionnaire, observational tool, direct measurement method) for the upper limbs and back in a truck assembly plant at two cycle times (11 and 8 min). The weighted Kappa factor showed fair agreement between the observational and direct measurement method for the arm (0.39) and back (0.47). The weighted Kappa factor for these methods was poor for the neck (0) and wrist (0) but the observed proportional agreement (P) was 0.78 for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
1
9
0
1
Order By: Relevance
“…Among limitations, different studies have shown that selfreported exposure to ergonomic factors in the workplace has only moderate reproducibility and validity for most physical exposures (54)(55)(56), which is expected to decrease further for exposures occurred in a distant past, with the consequence of a non-differential misclassification of the exposure and an underestimation of the association with health outcomes. This potential bias has likely reduced the association between exposure to ergonomic factors and low walking speed in our study, with the consequences of an underestimation of the proportion of the excess risk mediated by these factors.…”
Section: Limitationsmentioning
confidence: 99%
“…Among limitations, different studies have shown that selfreported exposure to ergonomic factors in the workplace has only moderate reproducibility and validity for most physical exposures (54)(55)(56), which is expected to decrease further for exposures occurred in a distant past, with the consequence of a non-differential misclassification of the exposure and an underestimation of the association with health outcomes. This potential bias has likely reduced the association between exposure to ergonomic factors and low walking speed in our study, with the consequences of an underestimation of the proportion of the excess risk mediated by these factors.…”
Section: Limitationsmentioning
confidence: 99%
“…Observational instruments have been developed and applied to identify and quantify ergonomic work exposures or risk factors, with metrics including e.g., postures, body segments, risk levels, perceived exertion or discomfort, job profiles and load etc., through direct observational methods, self-reporting, or direct objective measurement methods-or a combination of these [5][6][7][8][9][10][11][12][13][14][15][16][17]. Direct objective measurements are often favoured over observation and self-report [18] as self-report is known to be imprecise and potentially biased [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have criticized the reliability and repeatability of simple tools (Barrero, Katz, and Dennerlein 2009;Chiasson et al 2012;Zare et al 2017). The results of these tools have been often questioned because of inter and intra-individual variability, the variations of the technical-organizational system (e.g., unexpected mishaps/incidents arising from machines and materials), and the diversification of products (Badets, Merlo, and Pilniere 2017;Koukoulaki 2014;Mathiassen 2006; Sagot, and Roquelaure 2018).…”
Section: Introductionmentioning
confidence: 99%